Dual depolarization responses generated within the same lateral septal neurons by TRPC4-containing channels - Tian, Jin Bin; Freichel, Marc (Pflügers Archiv, 2014)
In the central nervous system, canonical transient receptor potential (TRPC) channels have been implicated in mediating neuronal excitation induced by stimulating metabotropic receptors, including group 1 metabotropic glutamate receptors (mGluRs). Lateral septal (LS) neurons express high levels of TRPC4 and group I mGluRs. However, to what extent native TRPC4-containing channels (TRPC4-cc) are activated as well as the impact of different levels of TRPC4-cc activation on neuronal excitability remain elusive. Here, we report that stimulating LS neurons with group I mGluR agonist, (S)-3,5-DHPG, causes either an immediate increase in firing rate or an initial burst followed by a pause of firing, which can be correlated with below-threshold-depolarization (BTD) or above-threshold-plateau-depolarization (ATPD), respectively, in whole-cell recordings. The early phase of BTD and the entire ATPD are completely absent in neurons from TRPC4−/− mice. Moreover, in the same LS neurons, BTD can be converted to ATPD at more depolarized potentials or with a brief current injection, suggesting that BTD and ATPD may represent partial and full activations of TRPC4-cc, respectively. We show that coincident mGluR stimulation and depolarization is required to evoke strong TRPC4-cc current, and Na+ and Ca2+ influx, together with dynamic changes of intracellular Ca2+, are essential for ATPD induction. Our results suggest that TRPC4-cc integrates metabotropic receptor stimulation with intracellular Ca2+ signals to generate two interconvertible depolarization responses to affect excitability of LS neurons in distinct fashions.
Published online: 13 October 2013
Gesehen am 21.09.2020